Exploring abortion laws: A case study of Bangladesh, India, Russia, and the United States - Kapoor, Pooja (Economic and Political Weekly)
Abortion has long been a divisive issue in the rights debate particularly when it is presented as a conflict between a woman$1 (Bs right to choose and an unborn child$1 (Bs right to live. Unsafe abortion can lead to long-term issues detrimental to woman$1 (Bs health and psychological well-being, in addition to acute health risks and even fatality. This paper offers a comprehensive overview of current abortion laws and practices in Bangladesh, India, Russia, and the US. While restrictive laws are often violated, few of them are appropriate for their intended purpose. It is important to acknowledge that the right to make independent decisions about her own body and reproductive functions is at the very core of the fundamental rights of women.- Reproduced s
Keywords: Abortion laws, Bangladesh, Russia, United States